Registry of Origin: Narrative and Passion Structure - Linkevičiūtė-Rimavičienė, Jolita (Semiotika, 2017)
The aim of this article is to discuss some texts which at the diffe-rent times constructed the Lithuanian nation’s cultural identity. We have drawn attention to the concept of national identity published in the periodical “Aušra” (1883). The narrative was created in the 19th century as an act of revolutionary social transformation in order to define the national consciousness, language and culture. More significantly, the site of cultural difference became the process of the enunciation of culture as “knowledgeable”, authoritative, adequate to the construction of systems of cultural identification. The enunciation of cultural difference problematizes the bina-ry division of past and present, tradition and modernity at the le-vel of cultural representation. It is the problem of how, in signifying the present, something comes to be repeated, relocated and translated in the name of tradition. Thus the political (and theoretical) genealogy of modernity lies not only in the origins of the idea of civility, but in this history of the colonial moment. We pay attention to the importance of the hybrid moment of political change and the time of enunciation and make the question of contradictions rooted in the process of translation and displacement in which the cultural identity was written. Applying semiotic approach we have rethink the cultural text or system of meanings as the Semantic Universe for recognition the structure of symbolization. In the purpose to understand the two familiar traditions in the discourse of identity we seized the space of representation, where the image of Self is confronted with the difference, its Other. The Subject (individual or nation) can construct himself only through the differences and he need the Other/Others for the reason of the semiotic existence. The experience of identity makes sense only via an articulation of difference: there is no Us without Them. A cultural unit exists and is recognized insofar as there exists another one which is opposed to it. We are faced with a dimension of double-dealing: a charge of assimilation and the act of eclude. To understand the differences of the historical writing and self-identification let’s compare the idea of the two texts: Motiejus Stryjkowski “Chronicle” and Albertas Vijūkas-Kojalowicz “Lithuanian history”, both written as historical narratives (and political myths) before “Aušra”. We have used Algirdas Julius Greimas semiotic point of view to understand the rules governing the narrative programming: it is now clear that the analysis of the discourse may disco-ver ideology. We must try to decipher myths, stories and folklore for the reason to identify the systems of values and how the models of behaviour (ability to act) impact on the style of life in the modern society. To ascertain the mythological code we have used to discuss Lithuanian folktale about the Fearless Hero in order to understand the narrative structures. The structure of this folktale might be used to discover the new order doctrine and the ideology in the text of periodical “Aušra” also for exploring and identifying the narrative and passion structures of the concrete discourse.